2018
DOI: 10.3389/fgene.2018.00661
|View full text |Cite
|
Sign up to set email alerts
|

Introducing WikiPathways as a Data-Source to Support Adverse Outcome Pathways for Regulatory Risk Assessment of Chemicals and Nanomaterials

Abstract: A paradigm shift is taking place in risk assessment to replace animal models, reduce the number of economic resources, and refine the methodologies to test the growing number of chemicals and nanomaterials. Therefore, approaches such as transcriptomics, proteomics, and metabolomics have become valuable tools in toxicological research, and are finding their way into regulatory toxicity. One promising framework to bridge the gap between the molecular-level measurements and risk assessment is the concept of adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Since the introduction of Adverse Outcome Pathways (AOPs) to support regulatory decision making for risk assessment of chemicals ( 24 ), the primary focus of AOP research groups has been capturing mechanistic data in written format. However, since the majority of biological processes described in AOPs are biological pathways that exist as pathway models on WikiPathways, the AOP Portal ( http://aop.wikipathways.org ) has been created to capture all pathways relevant to toxicological assessments ( 25 ). These molecular AOPs contribute to the understanding of AOPs and facilitate the use of various omics approaches in risk assessments ( 26 ).…”
Section: Pathway Curation Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the introduction of Adverse Outcome Pathways (AOPs) to support regulatory decision making for risk assessment of chemicals ( 24 ), the primary focus of AOP research groups has been capturing mechanistic data in written format. However, since the majority of biological processes described in AOPs are biological pathways that exist as pathway models on WikiPathways, the AOP Portal ( http://aop.wikipathways.org ) has been created to capture all pathways relevant to toxicological assessments ( 25 ). These molecular AOPs contribute to the understanding of AOPs and facilitate the use of various omics approaches in risk assessments ( 26 ).…”
Section: Pathway Curation Communitiesmentioning
confidence: 99%
“…One challenge lies in the unique rationale behind molecular AOPs, where biological processes are connected in a chain of Key Events (KEs) that make an AOP, rather than presenting one molecular pathway. Second, KEs often describe disturbances or adverse responses already captured in molecular pathways in WikiPathways ( 25 ) and therefore AOPs are modelled as meta-pathways. These combine pathway nodes and KE nodes in one data model, which is linked to the AOP-Wiki, https://aopwiki.org ).…”
Section: Pathway Curation Communitiesmentioning
confidence: 99%
“…The Key Event Relationships are linkages between adverse outcome pathway modules that provide scientific evidence supporting the relationships between examined substance and its toxic effects [ 20 ]. AOP approach for evaluation and assessment of the health risks associated with exposure to a chemical or compound is increasingly used in metadata analysis of existing knowledge [ 22 , 23 ]. Therefore, we used existing AOPs in an effort to synthetize and present information from systematic review of the reported MP/NPs adverse effects with focus on mechanistic relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Two main advantages of using toxicogenomics data for advancing AOP development are: i) the comprehensive data supports validation of MIEs and KEs by providing molecular level details, and ii) the data enables identification of sensitive biomarkers for targeted measurement of the KEs identified in the AOP [9,44]. Initiatives have been taken to link biological pathway databases, such as WikiPathways, to AOPs, which enables AOP-linked bioinformatics analysis of toxicogenomics data [13,45]. For example, a data fusion pipeline aiming to enrich AOPs with molecular detail was successfully applied to develop an AOP-linked molecular description of lung fibrosis, demonstrating that transcriptomics data captures early effects of exposure before the histological manifestation of an AO.…”
Section: Toxicogenomics For the Development Of Aopsmentioning
confidence: 99%